Guillén de Lampart's conspiracy: historical background of independence in the Viceroyalty of New Spain (17th century) - Arias Castro, Tomás Federico (2021)
On the occasion of the commemoration, in 2021, of the bicentennial of the independence feats of the different territories that made up the former Viceroyalty of New Spain, this article of historical research exposes a detailed set of factors (dates, individuals, sites, incidences, decisions, episodes, etc.) that occurred between the second half of the 16th century and the 17th century, as the first antecedents of Mexican autonomy. In this regard, the intricate trajectories of the pioneering character Guillén de Lampart, who was the direct precursor of the emancipatory actions of this New Hispanic region, are exposed with amplitude, which, together with a parallel series of disgraceful and ruinous motivations, were erected in the causes of its execution by the inquisitorial authorities, being also the only non-nineteenth-century hero, whose statue is located in the current Independence Column in Mexico City.